Fuzzy logic for decision-enablement: a novel context-awareness framework for smarter environments. (2017) - Rajaraajeswari, S.; Selvarani, R.; Raj, Pethuru; Mohanavadivu, P.
With the emergence of pioneering technologies and tools in the information and communication technology (ICT) space, our everyday environments (personal, social, professional, etc.) are deeply ICT-enabled to be smarter in their operations and offerings. Smarter healthcare is one shining example. Provisioning real-time and precision-centric healthcare facilities for people especially those who are in disabled, debilitated, and diseased conditions is being made possible with the impressive advancements (the growing array of smart sensors, digitised entities, wearables, robots, controllers, and other disposable and diminutive actuators). The growing variety and volume of connected devices enable remote diagnostics, real-time monitoring, measuring, and management by transmitting various body health parameters for ensuring perfect decision-making and medication. In this paper, we have described an adaptive framework leveraging the pivotal power of fuzzy logic, which is famous for rule-based decision-making, for accelerating the systematic realisation of smarter environments especially for the healthcare segment.